Van der Woude Syndrome: A Case Report - Sobhan Mishra1 , Shibasis Biswas2 , Shelly Mishra3 , Pankaj Kumar Panda4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Congenital lip pits are developmental defects that occur on the paramedian portion of the vermilion borderof the lower lip. They may be unilateral or bilateral and may occur as an isolated conditionor in associationwith cleft lip and or cleft palate. When the labial pits occur in association with cleftlip and/or palate thecondition is referred to as Van der Woude Syndrome. In 1845, Demarquay(1945) first described the lowerlip pit and postulated that the condition occurs due to the indentation of the central incisor. Later in 1954,Anne Van der Woude first reported the association of congenital pitsof the lower lip with cleft lip and palate.Congenital lower lip pits are present in 88% of all VWS patients, and in 65%–75% of the cases these areassociated with cleft lip and palate. The Van der Woude syndrome is a rare condition the phenomenon of acleft lip and cleft palate combined in the same pedigree makes it unique. The VDWS should be consideredin the differential diagnosis of cleft lip and palate. The dentist may be the first person to diagnose thissyndrome, and therefore,should be aware of its variable expressions. A proper treatment plan at the correcttime will help to satisfy the psychological and esthetic needs of the patients. Further, genetic counseling ishighly recommended.